The Influence of Company Characteristics on the Financial Performance of Commercial Banks Listed on the IDX for the 2019-2023 Period - Shine, Jeiver; Muhmin, Andi Hidayat (Yayasan Gema Bina Nusantara, 2025)
Banking plays a crucial role in today's society, from fund collection activities, providing loans, to other operations managed by banks that significantly affect the financial flow within the community. Therefore, individuals need to evaluate the financial performance of banking institutions. Based on this premise, this study aims to analyze the extent to which company characteristics, namely capital adequacy, asset quality, leverage, firm size, and firm age, affect the financial performance of banks in Indonesia, as proxied by Return on Assets (ROA). The analytical method employed in this study is multiple linear regression using secondary data, processed through statistical software. The population consists of 47 banks listed on the Indonesia Stock Exchange (IDX), with the sampling technique using non-probability sampling, resulting in a total of 20 banks as the sample. Based on the analysis results, the variables of capital adequacy, asset quality, leverage, firm size, and firm age simultaneously have a positive and significant effect on the financial performance of banks. Partially, capital adequacy and firm age have no significant effect on financial performance. Asset quality and leverage have a negative and significant effect, while firm size has a positive and significant effect on bank financial performance. Future research is expected to analyze other factors, both financial and non-financial, that may influence banking performance.